SUKUK ISTISHNA' FOR POST-DISASTERS REGIONAL DEVELOPMENT IN SUMATERA IN 2025 - Lia safrina; Hartanti Dewi Dewi; Uswatun Hasanah uswah; Annisaturrahmi Nisa (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2026)
Sumatra is the sixth-largest island in the world, located in the westernmost part of Indonesia. This island is known for its natural wealth, cultural diversity, and strategic role in the Indonesian economy through agricultural and plantation products. As of December 2025, Sumatra is currently experiencing an ecological emergency due to flash floods and landslides that hit Aceh, North Sumatra, and West Sumatra. More than 1,000 lives have been recorded, with hundreds missing, infrastructure has been paralyzed, bridges have been damaged, and thousands of residents have been isolated. Following the flash flood disaster, the need to accelerate infrastructure development and environmental recovery is urgent. Budget constraints in each affected region require additional funding for development. One way to do this is through sukuk istisna' (Islamic bonds). Sukuk helps overcome regional government budget constraints in handling post-disaster reconstruction, which requires large and rapid funding. The use of sukuk with an istisna' contract is an effective alternative financing solution for post-disaster reconstruction. Through this mechanism, the government can finance the construction of damaged disaster-resistant infrastructure, such as schools, hospitals, and bridges, by involving third parties as contractors.